Unhealthy weight control practice and related factors among female public college students in Harari Regional State, Ethiopia, 2019 - Jamie, Arif Hussen Jamie; Ahmed, Abdusemed Mohammed Ahmed (Universitas Ahmad Dahlan, 2023)
The aim of this study was to determine the magnitude of unhealthy weight control practice and related factors among female college adolescents in Harari region. A school based cross-sectional study was conducted among 290 female college adolescents who were randomly selected from two government colleges. A pre- tested self-administered questionnaire was used. Measurement was taken to calculate Body Mass Index. Data was entered, cleaned and analyzed using SPSS version 20. Anthropometric. In this study, the odds of getting engaged in unhealthy weight control practice was 7.21 times higher among those within perceived overweight group than adolescents in perceived normal weight group, [AOR =7.2; 95% CI =1.2-27.9]. Furthermore, female adolescents within dissatisfied group for middle torso had 1.43 times higher odds of getting engaged in unhealthy weight control practice than those within satisfied group, [AOR=1.4; 95% CI=1.1-1.9]. The findings of this study gave insight on the prevalence of unhealthy weight control practice among female college adolescents in Harari regional state. The study also have got significant association between perceived overweight, middle torso dissatisfaction and engagement in unhealthy weight control practice within the last 30 days among female college adolescents in Harari regional state.